(untitled) (UCC Law Journal, 2023)
The evolution of DNA sequencing and analysis has had an extensive impact on criminal justice in many jurisdictions because it provides an opportunity for crime laboratories to develop distinct personal profiles required to identify crime suspects. This is connected with Locard’s principle of exchange that perpetrators of crime usually leave traces at the crime scene and take traces from the crime scene along with them. DNA evidence has led to the arrest of previously unidentifiable perpetrators of the crime and the exoneration of wrongfully convicted persons. The functionality of DNA technology in criminal justice depends on the existence of a comprehensive DNA database. However, obtaining DNA samples from suspects has been challenged as a bio-invasion of the suspect’s right to privacy and cause of citizen stigmatization. DNA analysis is also susceptible to unscrupulous manipulations in forensic science laboratories. To avert potential legal challenges, countries with comprehensive DNA databases have evolved extensive regulatory frameworks to oversee the collection and retention of DNA samples of suspects. The collection of DNA samples in Nigeria for crime solving is still at a very elementary stage and a national DNA database does not exist. This paper aims to undertake a comparative legal analysis of relevant case laws as well as legislations in jurisdictions such as the United Kingdom, United States of America and South Africa to advance the argument that it has become imperative to put in place a regulatory framework that will control the collection and storage of DNA samples as well as dictate the conduct of forensic laboratory scientists. A national DNA database is vital to combat crime but it must be subject to a regulatory framework.